2021
DOI: 10.1111/nph.17685
|View full text |Cite
|
Sign up to set email alerts
|

Novel chemicals engender myriad invasion mechanisms

Abstract: Non-native invasive species (NIS) release chemicals into the environment that are unique to the invaded communities, defined as novel chemicals. Novel chemicals impact competitors, soil microbial communities, mutualists, plant enemies, and soil nutrients differently than in the species' native range. Ecological functions of novel chemicals and differences in functions between the native and non-native ranges of NIS are of immense interest to ecologists. Novel chemicals can mediate different ecological, physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 141 publications
0
17
0
Order By: Relevance
“…However, we could not rule out that other chemicals may also be able to enhance AM fungal growth and association with host plants. Moreover, many environmental factors such as temperature, nutrient availability, soil water and other microbes, and even plant neighbors, may also affect root exudation and chemicals as well as AM fungal growth (Badri & Vivanco, 2009; Yoneyama et al ., 2012; Kong et al ., 2018; de Vries et al ., 2019; Inderjit et al ., 2021). Furthermore, for plant invasion, selection may favor species that have high root exudation in nonnative ranges (Callaway & Ridenour, 2004), and escape from natural enemies (herbivores and pathogens) may alter plant chemical signals that are associated with root chemical exudates (Tian et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we could not rule out that other chemicals may also be able to enhance AM fungal growth and association with host plants. Moreover, many environmental factors such as temperature, nutrient availability, soil water and other microbes, and even plant neighbors, may also affect root exudation and chemicals as well as AM fungal growth (Badri & Vivanco, 2009; Yoneyama et al ., 2012; Kong et al ., 2018; de Vries et al ., 2019; Inderjit et al ., 2021). Furthermore, for plant invasion, selection may favor species that have high root exudation in nonnative ranges (Callaway & Ridenour, 2004), and escape from natural enemies (herbivores and pathogens) may alter plant chemical signals that are associated with root chemical exudates (Tian et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of plant-AM fungi interactions, Bunn et al (2015) found that the strength of invasive plant-AM fungal mutualisms may depend on species and functional group. Although many studies have examined the difference in plant-AM fungal mutualism between native and invasive species (Reinhart & Callaway, 2006;Awaydul et al, 2019), the role that chemicals released by plants play is unclear (Inderjit et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Second, native and invasive plants grown in soil containing heterogeneous forms of P may differ in their plasticity to adjust root architecture and allocation (Yang et al, 2020;Zhang et al, 2022), which both govern interactions with AMF (Bergmann et al, 2020). Third, invasive species may also release greater concentrations of root chemical signaling compounds, such as flavonoids and strigolactones than native species, enhancing communications with mycorrhizal fungi (Inderjit et al, 2021;.…”
Section: Variations In Plant-amf Interactions Induced By Soil P Formsmentioning
confidence: 99%
“…Root exudates are crucial for signaling between AM fungi and plants to initiate the symbiosis (Harrison, 2005) so this finding provides an important clue. Root exudates have been highlighted in invasion biology for other reasons, including allelopathy, perhaps contributing to the suppression of native plants and soil biota, including AM fungi (Inderjit et al ., 2021). An underlying mechanism for allelopathy‐driven impacts might be the biogeographic novelty of the chemicals, in that species that are evolutionarily naïve to certain biochemicals can be particularly vulnerable to them.…”
mentioning
confidence: 99%
“…show that: (1) exotic plant species invest more in producing and sending chemical signals to AM fungi than do native plants; (2) signals produced by nonnative plants are more effective at recruiting AM fungi to exotic plant roots than signals produced by native species, and most importantly; (3) recruiting more AM fungi corresponds with greater plant growth. Exotic invasive plant species out‐perform natives in many ways (Inderjit et al ., 2021), but if and how mutualism is involved in this superior performance remains an ecological frontier.
‘Do mutualisms become less beneficial over time to limit costs, and is there something about novelty, per se, in mutualistic relationships that we do not fully understand?’
…”
mentioning
confidence: 99%